Outdoor and indoor benzene evaluation by GC-FID and GC-MS/MS - Sousa, José A. (2013)
The evaluation of benzene in different environments such as indoor (with and without tobacco smoke), a city area, countryside, gas stations and near exhaust pipes from cars running on different types of fuels was performed. The samples were analyzed using gas chromatography (GC) with flame ionization detection (FID) and tandem mass spectrometric detection (MS/MS) (to confirm the identification of benzene in the air samples). Operating conditions for the GC-MS analysis were optimized as well as the sampling and sample preparation. The results obtained in this work indicate that i) the type of fuel directly influences the benzene concentration in the air. Gasoline with additives provided the highest amount of benzene followed by unleaded gasoline and diesel; ii) the benzene concentration in the gas station was always higher than the advisable limit established by law (5 μg m−3) and during the unloading of gasoline the achieved concentration was 8371 μg m−3; iii) the data from the countryside (Taliscas) and the urban city (Matosinhos) were below 5 μg m−3 except 5 days after a fire on a petroleum refinery plant located near the city; iv) it was proven that in coffee shops where smoking is allowed the benzene concentration is higher (6 μg m−3) than in coffee shops where this is forbidden (4 μg m−3). This method may also be helpful for environmental analytical chemists who use GC-MS/MS for the confirmation or/and quantification of benzene.